x^2-(-10)*x=-49 y^2-2*x=23

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[LaTeX]
 2              
x  - -10*x = -49
$$x^{2} - - 10 x = -49$$
 2           
y  - 2*x = 23
$$- 2 x + y^{2} = 23$$
Быстрый ответ
[LaTeX]
$$x_{1} = - \frac{23}{2} + \frac{1}{2} \left(- \sqrt[4]{265} \cos{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )} - \sqrt[4]{265} i \sin{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )}\right)^{2}$$
=
$$-5 + 2 \sqrt{6} i$$
=
-5 + 4.89897948556636*i

$$y_{1} = - \sqrt[4]{265} \cos{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )} - \sqrt[4]{265} i \sin{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )}$$
=
$$- \sqrt[4]{265} e^{\frac{i}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )}}$$
=
-3.82614823262898 - 1.28039458685589*i
$$x_{2} = - \frac{23}{2} + \frac{1}{2} \left(- \sqrt[4]{265} \cos{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )} + \sqrt[4]{265} i \sin{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )}\right)^{2}$$
=
$$-5 - 2 \sqrt{6} i$$
=
-5 - 4.89897948556636*i

$$y_{2} = - \sqrt[4]{265} \cos{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )} + \sqrt[4]{265} i \sin{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )}$$
=
$$- \sqrt[4]{265} e^{- \frac{i}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )}}$$
=
-3.82614823262898 + 1.28039458685589*i
$$x_{3} = - \frac{23}{2} + \frac{1}{2} \left(\sqrt[4]{265} \cos{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )} - \sqrt[4]{265} i \sin{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )}\right)^{2}$$
=
$$-5 - 2 \sqrt{6} i$$
=
-5 - 4.89897948556636*i

$$y_{3} = \sqrt[4]{265} \cos{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )} - \sqrt[4]{265} i \sin{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )}$$
=
$$\sqrt[4]{265} e^{- \frac{i}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )}}$$
=
3.82614823262898 - 1.28039458685589*i
$$x_{4} = - \frac{23}{2} + \frac{1}{2} \left(\sqrt[4]{265} \cos{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )} + \sqrt[4]{265} i \sin{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )}\right)^{2}$$
=
$$-5 + 2 \sqrt{6} i$$
=
-5 + 4.89897948556636*i

$$y_{4} = \sqrt[4]{265} \cos{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )} + \sqrt[4]{265} i \sin{\left (\frac{1}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )} \right )}$$
=
$$\sqrt[4]{265} e^{\frac{i}{2} \operatorname{atan}{\left (\frac{4 \sqrt{6}}{13} \right )}}$$
=
3.82614823262898 + 1.28039458685589*i